Low sensitivity of the COVID-19 antigen test (PANBIO™ COVID-19 Ag rapid test) to detect asymptomatic infections in health personnel of the National Institute of Respiratory Diseases - Becerril Vargas, Eduardo; Cojuc-Konigsberg, Gabriel; Alberto Mujica Sánchez, Mario; García Colín, María Del Carmen; Alfredo Camacho Corral, Daniel; Hansel Chávez Morales, Hugo; Aguirre Pineda, José Nicolas; Martínez Bravo, Eduardo; Ortiz Martínez, Alejandro; Martínez Orozco, José Arturo; Rodríguez-Sánchez, Victor Manuel; Ochoa, Jesús Ariel Mariscal; et al. (Frontiers in Medicine, 2022)
Background: COVID-19 requires an early diagnosis to optimize management and limit transmission. SARS-CoV-2 is able to spread effectively. Infected asymptomatic individuals have been found to be contagious. RT-qPCR is the currently recommended laboratory method for diagnosing acute infection. However, rapid antigen detection (RAD) tests are not only fast, but require less specialized training. The possibility of using RAD tests to identify asymptomatic patients is attractive, as it could effectively contribute to minimizing the hospital spread of SARS-CoV-2. The objective of the study was to determine the performance of RAD versus RT-qPCR for the detection of asymptomatic cases in INER health personnel. Methods: In order to follow WHO guidelines, generalized tests, a test station for health care workers was implemented on demand. A rapid test was carried out and a second sample was taken to be processed by RT-qPCR . With the results of both tests we conducted a retrospective study. Sensitivity, specificity, positive predictive value, negative predictive value and negative likelihood ratios were calculated. Results: A total of 1640 RAD tests were performed in health care workers (mean age was 39,69, 47% with a self-reported comorbidity). Participants provided 1640 valid RAD/RT-qPCR test pairs with 2% testing positive via RT-qPCR. 12 RAD samples were positive for SARS-CoV-2. Overall sensitivity of the PANBIO ™ COVID-19 Ag Rapid Test test was 35.2%. Conclusions: RADs are not recommended for the detection of asymptomatic cases due to low performance.